An Examination of the Values of Islamic Education and Western Secular Education: A Comparative Analysis - Mohammad Al Farabi; Fachri Husaini Hasibuan; Ahmad Maulana; Ahmad Rasyid As-Sya’i (STAI Hubbulwathan Duri, 2023)
This paper has discussed the importance of creating reflective dialogue across contemporary and diverse cultures of higher education to facilitate mutual understanding and a desire to relate more to one another. This research explores important aspects related to the educational crisis by reviewing the conceptions and values of Islamic and Western education. The method used qualitative research. The type of research is Library Research with descriptive analysis techniques. The analysis is carried out on data or content related to the theme of discussion and problems studied from library sources such as books and scientific journals. Data used books and related research. Previous research, notably Muhammad Syafiq Mughni and Yunus Abu Bakar, compares Islamic and Western secular education. Muhammad Syafiq and Yunus Abu Bakar discussed Islamic education theory and its consequences for its development. Nur studied western and Islamic education philosophies. This research found that Islamic and Western higher education values differ by presenting evidence of a reflective and critical educational legacy, so there is a need to revive the tradition of pedagogical curiosity to inspire the dialogue of cross-views that often occurs between Islam and the West, which allows both sides to acknowledge the differences in principles and reality and the inevitability of mutual understanding. Muslim higher education institutions that are emerging gradually, such as universities that are rapidly expanding, need to promote educational ideals of openness, critique, and conversation to instill an open paradigm of thinking and being scientific. This study emphasises the need to make Islamic Education Studies an integrative subject of empirical research and professional growth in Islamic and Western higher education institutions.